Subcutaneous occurrence of encysted Acanthocephala in an anuran amphibian from Brazil - do Carmo, Willison (2024)
Acanthocephalans, in their adult stage, are obligatory parasites of many types of vertebrates, including anuran amphibians. Their complex life cycle always involves an arthropod intermediate host but may include non-obligatory strategies that could improve transmission success, such as paratenic infections. In paratenic hosts, these parasites are normally found loose in the body cavity or encysted in internal organs. Here, we present the first report of acanthocephalans found encysted under the skin of an amphibian (i.e., external to its body cavity). The specimen, a clay robber frog [Haddadus binotatus (Spix, 1824)], had been collected in an Atlantic Forest area in southeastern Brazil. Upon examination of the frog, we recovered two specimens of acanthocephalan (Order Echinorhynchida) encysted under the skin of its venter. Considering the host’s relatively small size and its thin ventral musculature, we believe that the acanthocephalans may have accidentally trespassed the muscular tissue while attempting to encyst in the frog’s internal body wall.